Text and data mining exceptions in the development of generative AI models: What the EU member states could learn from the Japanese “nonenjoyment” purposes? - Artha Dermawan (The Journal of World Intellectual Property, 2023)
The European Union (EU) text and data mining (TDM) provisions are a progressive move, but the horizon is still uncertain for both generative artificial intelligence (GenAI) models researchers and developers. This article suggests that to drive innovation and further the commitment to the digital single market, during the national implementation, EU Member States could consider taking the Japanese broad, all-encompassing and “nonenjoyment-based” TDM as an example. The Japanese “nonenjoyment” purposes, however, are not foreign to the European continental view of copyright. A similar concept can be found under the German concept of “Freier Werkgenuss” or enjoyment of the work. A flexible TDM exception built upon the German notion of nonenjoyment purposes could become an opening clause to foster innovation and creativity in the age of GenAI. Moreover, the article argues that an opening clause allowing TDM with “nonenjoyment” purposes could be permissible under the so-called three-step test. This article further suggests, if there is no political will to safeguard “the right to read should be the right to mine” and to provide a welcoming environment for GenAI researchers and developers, when shaping the legal interpretation through national case law, the EU Member States could consider the following: (1) advocate for 720.167emh of response if technological protection measures (TPMs) are preventing TDM, and (2) Robot Exclusion Standard (robot.txt) as a warning when TDM is not allowed on a website. It is now in the hands of the EU Member States, whether to protect the interests of rightholders or to create a balance between safeguarding “the right to read should be the right to mine,” protecting rightholders exclusivity, and creating a supportive environment for the GenAI models researcher and developers.
Keywords: 340; copyright and related rights; freier werkgenuss; generative AI models; innovation; text and data mining